Givosiran, a novel treatment for acute hepatic porphyrias. Issue 1 (2nd January 2021) - Thapar, Manish; Rudnick, Sean; Bonkovsky, Herbert L.
ABSTRACT: Introduction: Acute hepatic porphyrias (AHPs) are a group of rare genetic disorders that affect the enzymes of the heme biosynthetic pathway. Patients have a varied presentation, but attacks of severe abdominal pain are the cardinal feature. Until recently, IV hemin was the only definitive treatment option available. Areas covered: We summarize salient features of AHP and the work leading to clinical studies of givosiran and to its approval by the US FDA and the EMA. Givosiran is a novel siRNA therapeutic agent that targets hepatic 5-aminolevulinic acid (ALA) synthase-1, the first and rate limiting enzyme in the heme biosynthetic pathway. It has been effective in decreasing the levels of hepatic ALA synthase-1 mRNA, levels of ALA, which likely is the chief neurotoxin, and the composite attack rates in patients with AHP. The drug can cause elevated liver enzymes, elevations in serum creatinine, and injection site reactions. Single doses, given to asymptomatic persons with AIP who are chronic high excretors of ALA and porphobilinogen, caused decreases in CYP1A2 and CYP2D6 activity, raising concern for drug interactions. Expert opinion: Givosiran is expensive; insurance plans are likely to limit its availability to patients with well-documented AHP and frequent and severe acute attacks.